Measurement of Natural and Artificial Radiation as Well as Radiation Applications in The Field of Medical Physics at SMA Negeri II Kuta Badung Bali - Gusti Ngurah Sutapa; I Gde Antha Kasmawan; Ida Bagus Made Suryatika; I Made Yuliara; Ni Nyoman Ratini; I Gusti Agung Ayu Ratnawati; Ni Luh Putu Trisnawati; I Ketut Putra; Ni Kadek Nova Anggarani (Kappa Journal, 2024)
The results of research that have been carried out, especially in the field of medical physics such as X-rays, have been widely utilized in the medical field, especially Radiology Units in Several General and Regional Hospitals. Thus, it is very important to be understood and known by the community, especially the community, in this case the students of SMA Negeri 2 Kuta. In 2022/2023, there are 507 male and 597 female students. Seeing these conditions, surveys and observations were carried out as a result, students had difficulty understanding physics because the physics subject matter was dense, memorized and mathematical. Seeing these results, it is necessary to carry out a new paradigm in physics learning. One of the more appropriate methods is to balance theory learning with field applications such as natural and artificial radiation measurements and applications in the field of medical physics. The results of natural radiation measurements in the classroom and outside the classroom were 0.605 ± 0.0024 and 0.182 ± 0.0008 mSv/year, respectively. The limit of the dosage rate allowed by BAPETEN is 1,000 mSv/year. Natural radiation identified in the classroom and outside the classroom is still declared safe